Investigating the iconicity of the AAC graphic symbols of Mulbery, ParticiPics and Talking Mats - Pampoulou, Eliada; Tsigka, Stella; Kadi, Evgenia; Kanari, Elpida; Georgiou, Savvina (My University, 2025)
Despite the fact that iconicity has been widely investigated, there is a lack of research focusing on collections of symbols that have relatively recently been developed. Since iconicity is related to symbols, referents, individuals, and instructional effects, which often interplay with each other, it is important to investigate some of these effects in isolation. For this study, the iconicity of Mulberry, ParticiPics and Talking Mats collections of symbols was investigated. Participants were 50 Greek-speaking undergraduate students unfamiliar with these particular graphic symbols. A mixed-method methodology focused on a 5-Likert scale that participants used to score the iconicity of the symbols presented from the three collections was adopted. This was followed by semi-structured interviews with all the participants. The statistical analysis of iconicity ratings across the three sets of symbols generated non-significant results for both comparisons: there was no statistically significant difference in iconicity ratings among the focal symbols. The comparison between verbs and nouns across the three symbol sets also showed no significant difference in iconicity ratings. Factors influencing the iconicity of symbols include color, component complexity, outline shape, static animation and word concreteness. These findings should be disseminated to symbol developers and clinicians.
Keywords: Graphic symbols; color; component complexity; iconicity; static animation